2015
DOI: 10.3389/fnhum.2015.00159
|View full text |Cite
|
Sign up to set email alerts
|

The first 1000 days of the autistic brain: a systematic review of diffusion imaging studies

Abstract: There is overwhelming evidence that autism spectrum disorder (ASD) is related to altered brain connectivity. While these alterations are starting to be well characterized in subjects where the clinical picture is fully expressed, less is known on their earlier developmental course. In the present study we systematically reviewed current knowledge on structural connectivity in ASD infants and toddlers. We searched PubMed and Medline databases for all English language papers, published from year 2000, exploring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 46 publications
5
33
0
Order By: Relevance
“…This is in accordance with the existing literature exploring brain structural connectivity in toddlers with ASD, showing an overall tendency to brain over-connectivity in ASD versus typically developing peers, observed at around 30 months of age, when autistic features start to be clinically detected, or even before [Conti et al, 2015]. This is in accordance with the existing literature exploring brain structural connectivity in toddlers with ASD, showing an overall tendency to brain over-connectivity in ASD versus typically developing peers, observed at around 30 months of age, when autistic features start to be clinically detected, or even before [Conti et al, 2015].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is in accordance with the existing literature exploring brain structural connectivity in toddlers with ASD, showing an overall tendency to brain over-connectivity in ASD versus typically developing peers, observed at around 30 months of age, when autistic features start to be clinically detected, or even before [Conti et al, 2015]. This is in accordance with the existing literature exploring brain structural connectivity in toddlers with ASD, showing an overall tendency to brain over-connectivity in ASD versus typically developing peers, observed at around 30 months of age, when autistic features start to be clinically detected, or even before [Conti et al, 2015].…”
Section: Discussionsupporting
confidence: 92%
“…Advanced connectivity studies are emerging in the literature reporting disrupted connectivity in toddlers with ASD, detectable even before the full phenotypic expression of the disorder [Conti et al, 2015]. At such a young age, head circumference has been consistently reported to show abnormal growth patterns in ASD Specifically, normal brain size at birth is probably followed by a rapid rate of growth in the first 2-4 years of life with a later normalization of head circumference [Courchesne et al, 2011a;Sacco et al, 2015].…”
Section: Introductionmentioning
confidence: 99%
“…19 More recent work further suggests that the “autistic brain” is characterized by hypo-connectivity rather than focal cortical abnormalities. 20 …”
Section: Discussionmentioning
confidence: 99%
“…Emerging findings from DTI studies in particular suggest that there are age-dependent atypicalities in the microstructural organization of white matter tracts in infants who later meet criteria for ASD [37]. Specifically, Wolff et al [38] identified higher fractional anisotropy (FA) at 6 months of age in high-risk infant siblings with later emerging ASD compared to infants without ASD; this increased in FA was followed by a slower rate of development in ASD infants such that by 24 months, ASD infants had lower values than infants without ASD.…”
Section: Early Markers Of Asd: What Have We Learned From Studies Of Tmentioning
confidence: 99%